KEDUDUKAN BAHASA MELAYU DALAM STORY TETRALOGI BURU KARYA PRAMOEDYA ANANTA TOER - Surya Putra, Hakim; Effendy, Chairil; Priyadi, A. Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractThis research is motivated by the purpose to describe the postition of Malay language in story of Buru Tetralogy by Pramoedya Ananta Toer. Focus of this research to describe the Malay language used, function of Malay language in the meaning of the totality of the text, and make a lesson plan in accordance with the research. This research uses descriptive method and the research form is qualitative. Data analysis steps used are data collection, data reduction, data presentation, data checking, data interpretation, and making conclusions. The results show that Malay language in story of Buru Tetralogy is included modern Malay and revolutionary Malay Language. Malay language by characters is not only limited to the language of daily communication, but also able to be a tool of struggle against Dutch colonialism, including through writing in Medan Priyayi newspaper. Malay Language in story of Buru Tetralogy also serves to give local color, culture, and become a tool of social control in society. Design instructional learning in Indonesian language study about the position of Malay Language in Buru Tetralogy can be applied to the students of class XII even semester.Â Keywords: Malay Language, Revolutionary, Politic